Factors Affecting the Rise of Online Thrift Stores in Kathmandu Valley - Maden, Maulikta; Rawat, Ramesh (Nepalese Journal of Finance, 2024)
This study examines the factors affecting the rise of online thrift stores in Kathmandu Valley. Consumer behavior and motivation is the dependent variable. The selected independent variables are social media, sustainable fashion, product information, affordability, and vintage items. The primary source of data is used to assess the opinions of respondents regarding social media, sustainable fashion, product information, affordability, and vintage items. The study is based on primary data of 120 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of factors affecting the rise of online thrift stores in Kathmandu Valley. The study showed a positive impact of social media on consumer behavior and motivation. It indicates that higher the use of social media, higher would be consumer behavior and motivation. Similarly, the study showed a positive impact of sustainable fashion on consumer behavior and motivation. It indicates that use of sustainable fashion leads to change in consumer behavior and motivation. Likewise, the study showed a positive impact of product information on consumer behavior and motivation. It indicates that reliable product information leads to change in consumer behavior and motivation. Further, the study showed a positive impact of affordability on consumer behavior and motivation. It indicates that affordable price of product motivate consumer to purchase the products. In addition, the study also showed a positive impact of vintage items on consumer behavior and motivation. It indicates that increase in vintage items leads to change in consumer behavior and motivation.